Feedback of GPS training data within professional English soccer: a comparison of decision making and perceptions between coaches, players and performance staff - Nosek, P.; Brownlee, T. E.; Drust, B.; Andrew, M. (Science and Medicine in Football, 2021)
Purpose: The aim of the study was to examine the perceptions of training data feedback from key stakeholders within the coaching process of professional soccer clubs. A survey assessed the importance of training data towards reflection and decision-making, potential barriers and player preferences.